Meeting (the) Pandemic: Videoconferencing Fatigue and Evolving Tensions of Sociality in Enterprise Video Meetings During COVID-19 - Bergmann, Rachel; Rintel, Sean; Baym, Nancy; Sarkar, Advait; Borowiec, Damian; Wong, Priscilla; Sellen, Abigail (Computer supported cooperative work, 2023)
When COVID-19 led to mandatory working from home, significant blind spots in supporting the sociality of working life—in the moment and over time—were revealed in enterprise video meetings, and these were a key factor in reports about videoconferencing fatigue. Drawing on a large study ( N = 849) of one global technology company’s employees’ experiences of all-remote video meetings during the COVID-19 pandemic, we use a dialectic method to explore the tensions expressed by employees around effectiveness and sociality, as well as their strategies to cope with these tensions. We argue that videoconferencing fatigue arose partly due to work practices and technologies designed with assumptions of steady states and taken-for-granted balances between task and social dimensions of work relationships. Our analysis offers a social lens on videoconferencing fatigue and suggests the need to reconceptualize ideas around designing technologies and practices to enable both effectiveness and sociality in the context of video meetings.